Level of maternal zinc serum as risk factor of preeclampsia - Tian Kaprianti; Putri Mirani; Abarham Martadiansyah; Theodorus Theodorus; Peby M. Lestari (Indonesian Socety of Obstetrics and Gynecology, 2022)
Objective : To know the relationship of serum zinc levels with preeclampsia (PE) Method: This observational research uses a type of case control research. The population of this study is all pregnant women with a single pregnancy, gestational age of 28-42 weeks who were treated at the Department of Obstetrics and Gynecology of RSUP Dr. Mohammad Hoesin Palembang from August 2020 to November 2020. The study divided into 2 group, a case group of 30 pregnant women with PE and a control group of 60 pregnant women non PE. Serum zinc level examination is performed on all samples that match the research criteria. The data is processed by using SPSS software program version 20.0 Windows. Result: Both case and control groups had no meaningful differences to the general characteristics of the patient. There were significant differences in average zinc levels of maternal serum in both research groups (p=0.013; 43.90 plus-minus 15.79 pg/dL). The value of serum zinc levels that have the best sensitivity and specificity is at 45.5 pg/dL. Conclusion: There is a meaningful relationship between serum zinc levels and PE events. Pregnant women with serum zinc levels greater than or equal to 45.5 pg /dL were significantly at 3.2 times more risk of PE than pregnant women with serum zinc levels less than or equal to 45.5 pg/dL. In this case it is necessary to supplement zinc earlier in pregnancy to reduce the risk of preeclampsia. Keywords: preeclampsia, zinc, case-control studies